HUBUNGAN ANTARA MANUSIA, MASYARAKAT, DAN BUDAYA DALAM PERSPEKTIF ISLAM - Zulkarnain Dali (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2016)
In life-paced world in the meantime, of course we are always in touch or need one samalainnya. It has become sunahtullah of the creator of the universe.  Therefore,  the following article will discuss  the relationship between man,  society  and  culture  are viewed  from the perspective of Islam. Certainly in this article  does  not discuss  in detail  the  relationship between the  three  items  above  in the  view of Islam,  but only discussed in general  terms